Determinant of Economic Growth - Badriah Sappewali; Basri Hasanuddin; Madris Iskandar; Fatmawati Fatmawati (Hasanuddin Journal of Business Strategy, 2022)
Economic growth is an economic problem in the long run that is affected by many factors. The aim of the research is to analyze the influence of government spending, investment, and net export on economic growth in Indonesia either directly or indirectly through the absorption of the labor force. The data in the research were secondary data of time series data from 2001 to 2020. They were obtained from Indonesia Bank, Statistic Center Bureau, and Capital Investment Coordination Bureau through internet facilities and other sources, i.e. journals and the results of research. The data were analyzed by using structural equation modeling (SEM). The results of the research reveal that the government’s spending and investment directly have a positive and significant influence on economic growth in Indonesia. Meanwhile, net export indirectly has a positive and significant influence on economic growth in Indonesia through the labor force. This implies that the government’s spending, investment, and net export are effective to support the increased economic growth in Indonesia.